Is Cultural Policy in Poland In the Process of Recentralization? - Katarzyna Kopeć (Transylvanian Review of Administrative Sciences, 2020)
One of the key mottos of system transformation in Poland after the fall of communism in 1989 was far-reaching decentralization. These transformation processes encompassed also the sector of culture. Now, this strong trend towards decentralization has been mitigated or even reversed. This paper will review many of the concerns which have been articulated in relation to the centralization/decentralization conundrum. The main aim of this paper is to test the assumption that cultural policy in Poland faces recentralization, by means of political, fiscal and administrative indicators to track the dynamics of its recent shifts. To look at this tendency I conducted a comparative analysis of the cultural policy instruments in two periods: the coalition of The Civic Platform and Polish People’s Party 2007- 2015, and Law and Justice Party 2015-2017. The study contributes to knowledge of political, fiscal and administrative settings of cultural policy recentralization in Poland.